2018
DOI: 10.3390/v10110638
|View full text |Cite
|
Sign up to set email alerts
|

Safety Studies of Pneumococcal Endolysins Cpl-1 and Pal

Abstract: Bacteriophage-derived endolysins have gained increasing attention as potent antimicrobial agents and numerous publications document the in vivo efficacy of these enzymes in various rodent models. However, little has been documented about their safety and toxicity profiles. Here, we present preclinical safety and toxicity data for two pneumococcal endolysins, Pal and Cpl-1. Microarray, and gene profiling was performed on human macrophages and pharyngeal cells exposed to 0.5 µM of each endolysin for six hours an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
(39 reference statements)
0
41
0
Order By: Relevance
“…Even though the effectiveness of endolysins has been demonstrated in vivo, there is a lack of research regarding their safety and toxicity. Nevertheless, safety studies carried out with endolysins Cpl-1 and PaI supported the safety of these compounds, since there was no significant pro-inflammatory response, hypersensitivity or allergic reaction after injecting 0.3 mg per mouse (15 mg/kg) of each protein (Harhala et al, 2018). Moreover, toxicity in mammals is not a worrying issue since it has been proven that intravenous administration of endolysin SAL-200 (highly similar to LysRODI) showed no signs of toxicity in rodents after single-and repeateddose experiments (Jun et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Even though the effectiveness of endolysins has been demonstrated in vivo, there is a lack of research regarding their safety and toxicity. Nevertheless, safety studies carried out with endolysins Cpl-1 and PaI supported the safety of these compounds, since there was no significant pro-inflammatory response, hypersensitivity or allergic reaction after injecting 0.3 mg per mouse (15 mg/kg) of each protein (Harhala et al, 2018). Moreover, toxicity in mammals is not a worrying issue since it has been proven that intravenous administration of endolysin SAL-200 (highly similar to LysRODI) showed no signs of toxicity in rodents after single-and repeateddose experiments (Jun et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Obviously, the safety and stability of endolysins must be considered ahead of their application to food products and in food processing facility systems. Therefore, studies exist in which the safety of the endolysins is reported; for example, after endolysin SAL-1, Cpl-1, and Pal injections, animals did not show mortality or signs of toxicity [54,55]. There are several studies of endolysins those introduced the potential for food applications ( Table 1).…”
Section: Food Safety Applications Of Endolysins As Biocontrol Agentsmentioning
confidence: 99%
“…As detailed here, numerous studies describe the characterization of new endolysins with activities against foodborne pathogens-not only in vitro, but also when applied to food and utensils. Moreover, a few studies have revealed the safety of these endolysins in relation to human health [54,55]. Taken together, endolysins are promising biocontrol agents that have the potential to be used in a variety of raw and processed foods as well as in food-producing facilities.…”
Section: Food Safety Applications Of Endolysins As Biocontrol Agentsmentioning
confidence: 99%
“…the lysin of interest) in silico and screen it for potential immunogenicity using mapping tools. (Jado et al 2003;Loeffler et al 2003;Harhala et al 2018 Upon detection of potential immunogenic regions, amino acids can be changed to reduce immunogenicity with minimal changes in protein conformation. Both aspects were incorporated into a single protein design tool, called EpiSweep (Parker et al 2013).…”
Section: Biochemical Modifications and Engineering To Reduce The Immumentioning
confidence: 99%
“…This branch of lysin engineering is only in its infancy and includes engineering efforts to reduce unwanted effects upon clinical administration. Examples of unwanted effects may include immune responses to the lysin upon (systemic) administration, a limited halflife, and proteolysis on the site of infection due to the presence of inflammatory proteases (Agren et al 2000;Jado et al 2003;Harhala et al 2018). These engineering approaches include both protein engineering and biochemical modifications through covalent attachment of specific groups.…”
Section: Introductionmentioning
confidence: 99%